Development of the relationship between visual selective attention and auditory change detection - Yuanjun Kong; Xuye Yuan; Yiqing Hu; Bingkun Li; Dongwei Li; Jialiang Guo; Meirong Sun; Yan Song (NeuroImage, 2025)
Understanding the developmental trajectories of the auditory and visual systems is crucial to elucidate cognitive maturation and its associated relationships, which are essential for effectively navigating dynamic environments. Our one recent study has shown a positive correlation between the event-related potential (ERP) amplitudes associated with visual selective attention (posterior contralateral N2) and auditory change detection (mismatch negativity) in adults, suggesting an intimate relationship and potential shared mechanism between visual selective attention and auditory change detection. However, the evolution of these processes and their relationship over time remains unclear. In this study, we recorded electroencephalography signals from 118 participants (42 adults and 76 typically developing children) during separate visual localization and auditory-embedded fixation tasks. Further, we employed both ERP analysis and multivariate pattern machine learning to investigate developmental patterns. ERP amplitude and decoding accuracy provided convergent evidence underlying a linear developmental trajectory for visual selective attention and an inverted U-shaped trajectory for auditory change detection from childhood to adulthood. Importantly, our findings confirmed the established association of an N2 pc-MMN in adults using a larger sample size, and further identified a positive correlation between decoding accuracy for visual target location and decoding accuracy for auditory stimulus type specifically in adults. However, both visual-auditory correlation effects were absent in children. Our study provides neurophysiological insights into the distinct developmental trajectories of visual selective attention and auditory change detection. It highlights that the close relationship between individual differences in the two processes emerges alongside their respective maturation and does not become evident until adulthood.